2011
DOI: 10.5402/2011/451020
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on the Efficiency of the Biostimulation with Autologous Plasma Rich in Platelet Growth Factors in Otorhinolaryngology: Otologic Surgery (Tympanoplasty Type I)

Abstract: When otologic procedures that involve tympanic membrane repairs are performed, biomaterials or biological tissues as normal as grafts are used. At the moment, biological material from the own patient is used with varying success rates. The procedure used and the patient's tissue repair capabilities tend to determine the outcome. We present a preliminary study on tympanic membrane perforation repairs using an autograft obtained by manipulating platelet degranulation and the coagulation cascade and reinforced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…We obtained similar results as Saynes-Marín, 19 who showed a success rate of closure about 88.5% after 6 week of follow up with functional improvement in 24 patients (70%) and were not reported side-effects or hearing loss using PRP as treatment. In our trial were 100% success rate at week six with no complications Also, Garin et al 20 informed functional results between 3 and 6 weeks after the application of platelet-rich fibrin comparing the audiometry performed within 2 weeks prior to the procedure and after it.…”
Section: Discussionsupporting
confidence: 85%
“…We obtained similar results as Saynes-Marín, 19 who showed a success rate of closure about 88.5% after 6 week of follow up with functional improvement in 24 patients (70%) and were not reported side-effects or hearing loss using PRP as treatment. In our trial were 100% success rate at week six with no complications Also, Garin et al 20 informed functional results between 3 and 6 weeks after the application of platelet-rich fibrin comparing the audiometry performed within 2 weeks prior to the procedure and after it.…”
Section: Discussionsupporting
confidence: 85%
“…The biostimulation effect of platelet-rich plasma on type 1 tympanoplasty studied by Navarrete Álvaro et al showed that platelet-rich plasma stimulates fibroblast and thus, aids in the closure of tympanic membrane perforations. 12…”
Section: Discussionmentioning
confidence: 99%
“…Although 53-94% of traumatic TM perforations have the potential for spontaneous recovery, some cases, albeit few in number, can result in persistent perforation and hearing loss [13,14]. Several studies have suggested that the healing process may be facilitated by patching with various materials, including paper, silk, and micropore strip tape [4][5][6]15].…”
Section: Discussionmentioning
confidence: 99%
“…Alvaro et al [14] reported successful healing after the use of PRP in three patients with eardrum perforations that had not healed spontaneously. El-Anwar et al [16] also reported successful results with the use of topical autologous PRP on Initial air and bone conduction thresholds are given for all the patients, final air and bone conduction thresholds are given for the patients whose perforation is closed.…”
Section: Discussionmentioning
confidence: 99%